LIPID OPTIMIZATION AMONG PATIENTS WITH PERIPHERAL ARTERY DISEASE FOLLOWING REVASCULARIZATION IN A SINGLE-CENTER COHORT - Franck H. Azobou Tonleu, MD (Elsevier, 2024)
Therapeutic Area: Peripheral Artery Disease Background: Lipid management is a cornerstone of peripheral artery disease (PAD) treatment to reduce major adverse cardiac events. The 2018 ACC/AHA cholesterol guidelines recommended statins, ezetimibe, and/or PCSK9 inhibitors in selected patients to reach a low density lipoprotein cholesterol (LDL-c) < 70 mg/dL. Methods: The cohort included all patients who underwent their index limb revascularization for PAD between 01/01/2021 and 12/31/2022 at a large urban safety net hospital. The cohort was created using ICD-10 and CPT codes. Lipid lowering medications and LDL-c were abstracted at baseline (prior to index revascularization) and at one year post index discharge. For baseline labs, we used values either prior or during (if no prior value) index revascularization. Results: The final cohort included 311 patients with 36% female, 49% Hispanic, 36% Black, and was 63 ± 10 years old. History of hypertension, hyperlipidemia, and type 2 diabetes were seen in 98%, 93%, and 79% of patients, respectively. Prior to revascularization, 78% of patients were on statins (53% high intensity, 22% moderate intensity), 7% on ezetimibe and no patients on PCSK-9i. By one year following revascularization, 94% were on statins (75% high intensity, 18% moderate intensity), 8% on ezetimibe, and no patients on PCSK-9i. Among 233 patients with baseline LDL-c, median was 81 mg/dL with 37% (86/233) with LDL-c < 70 mg/dL. Following revascularization, 132 patients had repeat lipid panel with median LDL-c 65 mg/dL and 55% (73/132) of them with LDL-c < 70 mg/dL. Conclusions: LDL-c optimization is a cornerstone of PAD management, especially in a post-revascularization population. In this cohort, there was increase in both overall statin use and use of high intensity by 1 year following revascularization. However, only 42% of patients had repeat lipid panel following revascularization and the use of non-statin therapies remained low despite only half achieving targeted LDL-C. These findings highlight an important care gap, and revascularization as an important opportunity for lipid optimization. Clinician education and EHR (Electronic Health Record) interventions could be leveraged to improve outcomes in this population.